Socialization of sustainable Pagar Alam Coffee Farming using herbicide reductors - Irmeilyana Irmeilyana; Ngudiantoro Ngudiantoro; Sri Indra Maiyanti (University of Merdeka Malang, 2022)
Many factors affect the low coffee production, including the lack of knowledge and education of farmers about weed control and proper maintenance of coffee plants. Herbicide reductant is a product made from organic as an herbicide-reducing agent so that it can reduce herbicide residue in agricultural areas while being more economical. The community service program aims to socialize and provide knowledge to coffee farmers about the importance of environmentally friendly coffee plantation land cultivation, especially in reducing the dose of herbicides used in weed control. The implementation of the activity was carried out through field studies by filling out questionnaires and interviews in Rimba Candi Village, Dempo Tengah District, Pagar Alam City. Field studies are also a means of socializing environmentally friendly agricultural land processing methods. Coffee farmers have realized the importance of using reducing herbicides for weed control and can apply herbicides properly, at the right dose, at the right target, in the right way, and at the right time. The majority of farmers are better educated than the use of reducing agents can overcome weed control problems more efficiently and effectively, so as to minimize the negative impact of coffee cultivation.